2014
DOI: 10.1016/j.drugpo.2014.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Within-prison drug injection among HIV-infected Ukrainian prisoners: Prevalence and correlates of an extremely high-risk behaviour

Abstract: Background In Ukraine, HIV-infection, injection drug use, and incarceration are syndemic; however, few services are available to incarcerated people who inject drugs (PWIDs). While data are limited internationally, within-prison drug injection (WP-DI) appears widespread and may pose significant challenges in countries like Ukraine, where PWIDs contribute heavily to HIV incidence. To date, WP-DI has not been specifically examined among HIV-infected prisoners, the only persons that can transmit HIV. Methods A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 57 publications
5
38
0
1
Order By: Relevance
“…This finding is supported from qualitative data in Ukrainian PWID who perceive that OAT is a treatment of last resort and should be reserved only for those who have no other options (67). It is important to note that our study was the first to inquire about and compare addiction severity during the time of incarceration with PLH who were currently incarcerated, and thus findings here complement previous research on within-prison drug use as reported by a sample of recently released prisoners (68). …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This finding is supported from qualitative data in Ukrainian PWID who perceive that OAT is a treatment of last resort and should be reserved only for those who have no other options (67). It is important to note that our study was the first to inquire about and compare addiction severity during the time of incarceration with PLH who were currently incarcerated, and thus findings here complement previous research on within-prison drug use as reported by a sample of recently released prisoners (68). …”
Section: Discussionsupporting
confidence: 75%
“…Group 2 had been recently released from prison. More details about the recruitment process (41) have been described previously. Briefly, for Group 1, the prison first provided a list of all HIV-infected prisoners, then a random sample generator provided a list that was used to recruit for interviews.…”
Section: Methodsmentioning
confidence: 99%
“…For opioid injectors, opioid substitution therapy (OST) with either methadone or buprenorphine remains the single most effective therapy to reduce HIV transmission. Recent data from Ukraine suggest that in the absence of prison-based OST, the prevalence of within-prison drug injection among PLWHA is extraordinarily high and often involves multiple sharing partners [15, 16]. Our data support within-prison HIV transmission since we minimally identify three instances of seroconversion during the current incarceration.…”
Section: Discussionsupporting
confidence: 60%
“…Treatment of SUDs in EECA, mostly as vestiges of antiquated influences from the former Soviet Union, has been restricted more by moral biases and prejudices than by scientific evidence (Bojko, Dvoriak, & Altice, 2013; Cohen, 2010a, 2010b). Without evidence-based interventions (EBIs) (Fazel & Baillargeon, 2011), detained persons often engage in risky HIV behaviors both within prison and post-release (Izenberg et al, 2014; Rhodes, 2002), creating a high-risk environment.…”
Section: Introductionmentioning
confidence: 99%
“…Police harassment practices toward PWIDs, though, have been reported as a substantial contributor to the suboptimal OAT scale-up (Bachireddy et al, 2014; Izenberg et al, 2014; Polonsky et al, 2015; Zabransky, Mravcik, Talu, & Jasaitis, 2014) both through preventing PWIDs from initiating treatment and creating barriers to retention in care.…”
Section: Introductionmentioning
confidence: 99%